Targeting the MAPK signaling pathway: implications and prospects of flavonoids in 3P medicine as modulators of cancer cell plasticity and therapeutic resistance in breast cancer patients - Peter Kubatka; Bianka Bojkova; Natalia Nosalova; Mykhailo Huniadi; Samson Mathews Samuel; Bini Sreenesh; Gabriela Hrklova; Karol Kajo; Slavomir Hornak; Dasa Cizkova; Rostyslav Bubnov; Ivica Smokovski; et al. (EPMA Journal, 2025)
Cancer drug resistance poses a significant challenge in oncology, primarily driven by cancer cell plasticity, which promotes tumor initiation, progression, metastasis, and therapeutic evasion in many different cancers. Breast cancers (BCs) are a prominent example of that, with an estimated 2.3 million new cases and 670,000 BC-related deaths registered worldwide annually. Triple-negative BC is especially challenging for treatments demonstrating particularly aggressive disease course, an early manifestation of metastatic disease, frequent drug-resistant cancer types, and poor individual outcomes. Although chemosensitizing agents have been developed, their clinical utility in oncology remains unproven. The mitogen-activated protein kinase (MAPK) pathway is considered a critical regulator of intracellular and extracellular signaling highly relevant for both — genetic and epigenetic modifications. Dysregulation of the MAPK signaling pathways plays a significant role in conferring chemoresistance in BC. Contextually, targeting the MAPK pathway represents a promising strategy for overcoming drug resistance and enhancing the therapeutic efficacy of anticancer agents in BC treatment. On the other hand, flavonoids, a prominent class of phytochemicals, are key modulators of MAPK signaling. Flavonoids interact with the ERK, JNK, p38, and ERK5 pathways of the MAPK signaling cascade and present a promising avenue for developing novel anti-cancer therapies and re-sensitizing agents for the treatment of BC. Compounds such as quercetin, kaempferol, genistein, luteolin, myricetin, EGCG, baicalein, baicalin, nobiletin, morin, delphinidin, acacetin, isorhamnetin, apigenin, silymarin, among others, have been identified as specific modulators of MAPK signaling, exerting complex downstream effects in BC cells increasing therewith drug efficacy and suppressing tumor growth and aggressivity. These properties reflect mechanisms of great clinical relevance to overcome therapeutic resistance in overall BC management. This article highlights corresponding mechanisms and provides clinically relevant illustrations in the framework of 3P medicine for primary (protection of individuals at high risk against health-to-disease transition) and secondary care (protection against metastatic BC progression). 3PM novelty makes good use of patient phenotyping and stratification, predictive multi-level diagnostics, and application of Artificial Intelligence (AI) tools to the individualized interpretation of big data — all proposed for cost-effective treatments tailored to individualized patient profiles with clear benefits to patients and advanced BC management.

B7-H3 at the crossroads between tumor plasticity and colorectal cancer progression: a potential target for therapeutic intervention - Elizabeth Varghese; Samson Mathews Samuel; Aranka Brockmueller; Mehdi Shakibaei; Peter Kubatka; Dietrich Büsselberg (Cancer and Metastasis Reviews, 2024)
B7-H3 (B7 homology 3 protein) is an important transmembrane immunoregulatory protein expressed in immune cells, antigen-presenting cells, and tumor cells. Studies reveal a multifaceted role of B7-H3 in tumor progression by modulating various cancer hallmarks involving angiogenesis, immune evasion, and tumor microenvironment, and it is also a promising candidate for cancer immunotherapy. In colorectal cancer (CRC), B7-H3 has been associated with various aspects of disease progression, such as evasion of tumor immune surveillance, tumor-node metastasis, and poor prognosis. Strategies to block or interfere with B7-H3 in its immunological and non-immunological functions are under investigation. In this study, we explore the role of B7-H3 in tumor plasticity, emphasizing tumor glucose metabolism, angiogenesis, epithelial-mesenchymal transition, cancer stem cells, apoptosis, and changing immune signatures in the tumor immune landscape. We discuss how B7-H3-induced tumor plasticity contributes to immune evasion, metastasis, and therapy resistance. Furthermore, we delve into the most recent advancements in targeting B7-H3-based tumor immunotherapy as a potential approach to CRC treatment.

Resveratrol as sensitizer in colorectal cancer plasticity - Aranka Brockmueller; Anjana Sajeev; Lenka Koklesova; Samson Mathews Samuel; Peter Kubatka; Dietrich Büsselberg; Ajaikumar B. Kunnumakkara; Mehdi Shakibaei (Cancer and Metastasis Reviews, 2024)
Despite tremendous medical treatment successes, colorectal cancer (CRC) remains a leading cause of cancer deaths worldwide. Chemotherapy as monotherapy can lead to significant side effects and chemoresistance that can be linked to several resistance-activating biological processes, including an increase in inflammation, cellular plasticity, multidrug resistance (MDR), inhibition of the sentinel gene p53, and apoptosis. As a consequence, tumor cells can escape the effectiveness of chemotherapeutic agents. This underscores the need for cross-target therapeutic approaches that are not only pharmacologically safe but also modulate multiple potent signaling pathways and sensitize cancer cells to overcome resistance to standard drugs. In recent years, scientists have been searching for natural compounds that can be used as chemosensitizers in addition to conventional medications for the synergistic treatment of CRC. Resveratrol, a natural polyphenolic phytoalexin found in various fruits and vegetables such as peanuts, berries, and red grapes, is one of the most effective natural chemopreventive agents. Abundant in vitro and in vivo studies have shown that resveratrol, in interaction with standard drugs, is an effective chemosensitizer for CRC cells to chemotherapeutic agents and thus prevents drug resistance by modulating multiple pathways, including transcription factors, epithelial-to-mesenchymal transition-plasticity, proliferation, metastasis, angiogenesis, cell cycle, and apoptosis. The ability of resveratrol to modify multiple subcellular pathways that may suppress cancer cell plasticity and reversal of chemoresistance are critical parameters for understanding its anti-cancer effects. In this review, we focus on the chemosensitizing properties of resveratrol in CRC and, thus, its potential importance as an additive to ongoing treatments. Graphical abstract

Antithrombotic and antiplatelet effects of plant-derived compounds: a great utility potential for primary, secondary, and tertiary care in the framework of 3P medicine - Peter Kubatka; Alena Mazurakova; Lenka Koklesova; Marek Samec; Juraj Sokol; Samson Mathews Samuel; Erik Kudela; Kamil Biringer; Ondrej Bugos; Martin Pec; Barbara Link; Marian Adamkov; et al. (EPMA Journal, 2022)
Thromboembolism is the third leading vascular disease, with a high annual incidence of 1 to 2 cases per 1000 individuals within the general population. The broader term venous thromboembolism generally refers to deep vein thrombosis, pulmonary embolism, and/or a combination of both. Therefore, thromboembolism can affect both – the central and peripheral veins. Arterial thromboembolism causes systemic ischemia by disturbing blood flow and oxygen supply to organs, tissues, and cells causing, therefore, apoptosis and/or necrosis in the affected tissues. Currently applied antithrombotic drugs used, e.g. to protect affected individuals against ischemic stroke, demonstrate significant limitations. For example, platelet inhibitors possess only moderate efficacy. On the other hand, thrombolytics and anticoagulants significantly increase hemorrhage. Contextually, new approaches are extensively under consideration to develop next-generation antithrombotics with improved efficacy and more personalized and targeted application. To this end, phytochemicals show potent antithrombotic efficacy demonstrated in numerous in vitro, ex vivo, and in vivo models as well as in clinical evaluations conducted on healthy individuals and persons at high risk of thrombotic events, such as pregnant women (primary care), cancer, and COVID-19-affected patients (secondary and tertiary care). Here, we hypothesized that specific antithrombotic and antiplatelet effects of plant-derived compounds might be of great clinical utility in primary, secondary, and tertiary care. To increase the efficacy, precise patient stratification based on predictive diagnostics is essential for targeted protection and treatments tailored to the person in the framework of 3P medicine. Contextually, this paper aims at critical review toward the involvement of specific classes of phytochemicals in antiplatelet and anticoagulation adapted to clinical needs. The paper exemplifies selected plant-derived drugs, plant extracts, and whole plant foods/herbs demonstrating their specific antithrombotic, antiplatelet, and fibrinolytic activities relevant for primary, secondary, and tertiary care. One of the examples considered is antithrombotic and antiplatelet protection specifically relevant for COVID-19-affected patient groups.

Homocysteine metabolism as the target for predictive medical approach, disease prevention, prognosis, and treatments tailored to the person - Lenka Koklesova; Alena Mazurakova; Marek Samec; Kamil Biringer; Samson Mathews Samuel; Dietrich Büsselberg; Peter Kubatka; Olga Golubnitschaja (EPMA Journal, 2021)
Homocysteine (Hcy) metabolism is crucial for regulating methionine availability, protein homeostasis, and DNA-methylation presenting, therefore, key pathways in post-genomic and epigenetic regulation mechanisms. Consequently, impaired Hcy metabolism leading to elevated concentrations of Hcy in the blood plasma (hyperhomocysteinemia) is linked to the overproduction of free radicals, induced oxidative stress, mitochondrial impairments, systemic inflammation and increased risks of eye disorders, coronary artery diseases, atherosclerosis, myocardial infarction, ischemic stroke, thrombotic events, cancer development and progression, osteoporosis, neurodegenerative disorders, pregnancy complications, delayed healing processes, and poor COVID-19 outcomes, among others. This review focuses on the homocysteine metabolism impairments relevant for various pathological conditions. Innovative strategies in the framework of 3P medicine consider Hcy metabolic pathways as the specific target for in vitro diagnostics, predictive medical approaches, cost-effective preventive measures, and optimized treatments tailored to the individualized patient profiles in primary, secondary, and tertiary care.

Flavonoids against the Warburg phenotype—concepts of predictive, preventive and personalised medicine to cut the Gordian knot of cancer cell metabolism - Marek Samec; Alena Liskova; Lenka Koklesova; Samson Mathews Samuel; Kevin Zhai; Constanze Buhrmann; Elizabeth Varghese; Mariam Abotaleb; Tawar Qaradakhi; Anthony Zulli; Martin Kello; Jan Mojzis; et al. (EPMA Journal, 2020)
The Warburg effect is characterised by increased glucose uptake and lactate secretion in cancer cells resulting from metabolic transformation in tumour tissue. The corresponding molecular pathways switch from oxidative phosphorylation to aerobic glycolysis, due to changes in glucose degradation mechanisms known as the ‘Warburg reprogramming’ of cancer cells. Key glycolytic enzymes, glucose transporters and transcription factors involved in the Warburg transformation are frequently dysregulated during carcinogenesis considered as promising diagnostic and prognostic markers as well as treatment targets. Flavonoids are molecules with pleiotropic activities. The metabolism-regulating anticancer effects of flavonoids are broadly demonstrated in preclinical studies. Flavonoids modulate key pathways involved in the Warburg phenotype including but not limited to PKM2, HK2, GLUT1 and HIF-1. The corresponding molecular mechanisms and clinical relevance of ‘anti-Warburg’ effects of flavonoids are discussed in this review article. The most prominent examples are provided for the potential application of targeted ‘anti-Warburg’ measures in cancer management. Individualised profiling and patient stratification are presented as powerful tools for implementing targeted ‘anti-Warburg’ measures in the context of predictive, preventive and personalised medicine.

Novel role of NADPH oxidase in ischemic myocardium: a study with Nox2 knockout mice - Mahesh Thirunavukkarasu; Ram Sudheer Adluri; Bela Juhasz; Samson Mathews Samuel; Lijun Zhan; Anupinder Kaur; Gautam Maulik; Juan A Sanchez; Janet Hager; Nilanjana Maulik (Functional & Integrative Genomics, 2012)